The molecular dynamics study of vacancy defect influence on carbon nanotube performance as drug delivery system - Li, Shuai; Sajadi, S. Mohammad; Alharbi, Khalid Abdulkhaliq M; El-Shorbagy, M.A.; Tlili, Iskander (Engineering analysis with boundary elements, 2022)
In the current research, we described atomic vacancy defect influence on nanopumping performance of CNT structure with molecular dynamics (MD) method (for the first time). In our simulations, CNT structure is defined in the presence of C20 molecule and Au tips in the nanopumping process. Temperature and potential energy convergence after 1 ns indicated the atomic stability in defined systems, which this result arises from the appropriate settings inside the MD box. Also, the nanopumping process was detected after 0.26 ps for the CNT structure without any vacancy defect. By atomic defect implementation to C-based nanotube, the nano-pumping performance of this tube was disrupted. Numerically, by inserting 1% vacancy to pristine CNT, the nanopumping was detected after 0.29 ps. Furthermore, MD outputs predicted by implementing vacancy defect with a larger 10% ratio, nanopumping process doesn't occur. On the other hand, by nanopumping parameters optimization in defected CNT (with 1% defect), this atomic process (nanopumping) occurs after 0.24 ps.